Tailings dam closure and declassification: closure optimisation with limited rehabilitation resources - Kemp, A.; Chapman, P. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Mine waste landforms will become part of the landscape in perpetuity. Detailed investigations and engineering design considering environmental factors are required before their implementation, and should be followed by monitoring and eventually relinquishment, if achievable. Some consequences of not undertaking the required investigations and design assessments before closure construction are that acceptable environmental and financial outcomes are not achieved and/or the end user or engineer of record (EOR) for a tailings storage facility (TSF) does not agree with, or accept responsibility for, the closure design or constructed closure landform. The TSF owner’s objective is to deliver optimised closure outcomes for their sites. The optimised closure outcome for a site may be one of the following or a combination: using the site for an alternative land use, ongoing management, relinquishment or divestment. Closure of this TSF aligned with their approach to risk management for TSFs and supported their aspiration to leave a sustainable and positive legacy. The ~215 ha TSF site is located in the Pilbara region of Western Australia. Most of the tailings had been removed from the TSF for reprocessing. The TSF still required EOR oversight as safety risks (some credible failure modes) remained. These were associated with open water ponding and stormwater containment, including freeboard requirements, and the risk of embankment overtopping and embankment/dam breach which could release tailings. Originally there was a lack of tailings and borrow material characterisation and quantification. Investigations undertaken to support closure design included material sampling, geochemical and physical testing and characterisation, and quantification of tailings. Initially the proposed end land use was focused on industrial use based on property zoning. A concept was developed that included multiple layers of cement-stabilised tailings with minimal growth media cover. The limited growth media thickness and lack of surface erosion modelling presented an unacceptable risk to the end user. An optimised design, including surface erosion assessment, resulted in an increased growth media cover thickness using materials from within the TSF footprint, which reduced the cement stabilisation requirements and, therefore, closure construction cost. Construction drawings were produced for implementation. The TSF has recently been closed and declassified as a dam as no credible failure modes remain.